2017
DOI: 10.1080/21645515.2017.1293769
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge, attitudes and practices on influenza among medical college students in Northwest China

Abstract: Objective This study aimed to understand the knowledge, attitudes and practices (KAP) on seasonal influenza among medical college students in a low-income multiethnic society. Methods A cross-sectional questionnaire survey collected information of KAP related to influenza. A knowledge score was calculated according to the total number of correct points out of 9 questions. Logistic regression was used to identify factors associated with influenza vaccine uptake. Results 856 valid questionnaires were obtained. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
2
27
0
2
Order By: Relevance
“…China is one of the 22 countries in the world that feature a high TB rate, with incidence in 2015 reaching 63.4 out of 10,000 and mortality in 2014 totaling 2.32 out of 100,000 [ 3 ]. In China, influenza is highly infectious and strongly epidemic or pandemic among young people [ 4 ]. Mumps is a common respiratory infectious disease in children and adolescents [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…China is one of the 22 countries in the world that feature a high TB rate, with incidence in 2015 reaching 63.4 out of 10,000 and mortality in 2014 totaling 2.32 out of 100,000 [ 3 ]. In China, influenza is highly infectious and strongly epidemic or pandemic among young people [ 4 ]. Mumps is a common respiratory infectious disease in children and adolescents [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, emotions experienced at the point of decision-making may be as important in health behaviour as a cognitive assessment of the risk, such as worry and anticipated regret, which have also been shown to be predictive of influenza vaccination [20] , [25] , [26] . Few studies have used the HBM to study influenza vaccine behaviour in LMICs [27] , [28] , [29] , [30] , [31] .…”
Section: Introductionmentioning
confidence: 99%
“…In the pre-intervention phase, the total KAP scores for students group (mean rank = 166·6) and non-students group (mean rank = 235·1) were statistically significantly different and displayed a median of 12 (IQR = 9·5-14) in students group and 14 (IQR = 11-17) in non-students group, respectively. In the post-intervention phase, the total KAP scores for students group (mean rank = 176·4) and non-students group (mean rank = 167·1) were not statistically significantly different and displayed a median of 17 (IQR = [15][16][17][18][19] in students group and 17 (IQR = 13-19) in nonstudents group, respectively. Based on these results, it can be assumed that the intervention programme had a better effect on students group.…”
Section: Impact Of the Intervention Programme On Kap Of Students Andmentioning
confidence: 94%
“…We assessed KAP of respondents regarding SFTS based on their responses to the questionnaire provided. Table 2 shows the median (IQR) of KAP and total KAP score was 3 (1-5), 8 (6·5-9), 3 (2-3) and 13 (11)(12)(13)(14)(15)(16)(17) in the pre-invention phase and 5 (3-7), 10 (7-10), 3 (3-3) and 17 (14)(15)(16)(17)(18)(19) in the post-invention phase, respectively. The results indicated that there was a significant increase in the four type scores (Ps < 0·001).…”
Section: Impact Of the Intervention Programme On Knowledgementioning
confidence: 99%
See 1 more Smart Citation